(3GdhSGFd GdbGfhfjI decGaMI GdeeGQSGJ GdGMJcGQjI hMeGjI GdefGaSI (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQi hGdJTQjYGJ GdCeQjcjI GdebGHdI (B/ s - (3CejQI YHOGdZaGQ eMeO CHhRjO s; (3eMehO eNJGQ CMeO HQHQi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JYbO GdQSGdI ebGQfI Hjf GdJTQjYGJ GdGeQjcjI HTCf MeGjI GdefGaSI hefY GdeeGQSGJ GdGMJcGQjI hGdbGfhf GdeUQi ef MjK fhYjI hWHjYI GdGaYGd hGdeeGQSGJ GdeLQeI bGfhfG hfWGb JWHjb GdbGfhf hGdGLgRI GdGOGQjI GdbGFeI Ydi JWHjb GdbGfhf hUdGMjGJgG hGdYbhHGJ Ydi GdGaYGd hGdeeGQSGJ GdeMXhQI bGfhfG hGdGYaGAGJ GdJi GbQJgG cdG ef GdJTQjYGJ GdGeQjcjI hGdbGfhf GdeUQi Ke fbhe HhVY JYdjb Ydi GdbGfhf eUQi HgOa JhVjM fbGW GdVYa GdJi JThH GdbGfhf hJbOje JhUjGJ HTCfgG (B. (3hYQV dYOI bhGfjf eUQjI JJVef fUhU eJaQbI HTCf MeGjI GdefGaSI hfWGb JWHjbgG Ke YQV dGMcGe UGOQI ef eMceI GdfbV GdeUQjI jQLY JGQjNgG Edi YGe (B1926s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdeeGQSGJ GdGMJcGQjI s; (3GdefGaSI ZjQ GdeTQhYIs; (3GfhGY GdGMJcGQ s; (3GdeQcR GdeSjWQs; (3dLfI GdJLGQI GdajOQGdjIs; (3GdNUNUIs; (3bVjI GdGSefJs; (3bVjI MOjO GdJSdjMs; (3bGfhf TjQeGfs; (3bGfhf cdGjJhfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs